Analisis Layanan Konseling Kelompok dengan Teknit Behavorial Contract dalam Mereduksi Perilaku Prokrastinasi Siswa di SMP - Yustin Laapadang; Junyathi Pasangka (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
This study aims to analyze group counseling services using the behavioral contract technique in reducing students' procrastination behavior at the junior high school level. Academic procrastination is a common problem among students, characterized by delaying task completion, lack of study discipline, and poor time management skills. This research employs a qualitative approach with a library research method by examining various relevant sources such as books, scientific journals, and articles. The data analysis technique used is content analysis to obtain a comprehensive understanding of the concept and implementation of the behavioral contract technique in group counseling. The results of the study indicate that group counseling services are effective in helping students understand and overcome procrastination behavior through supportive group dynamics. The application of the behavioral contract technique is proven to enhance students’ commitment, discipline, and responsibility in completing academic tasks. In addition, the reinforcement system within the behavioral contract encourages students to maintain positive behavior consistently. Therefore, group counseling with the behavioral contract technique can be considered an effective strategy to reduce students' academic procrastination at the junior high school level.